Exploring the interaction between Kendari’s economic growth and its hinterland - Anggraini, Yuyun; Prima, Suci Rahmawati; Triani, Neks; Hariono, Hariono (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
In order to attain high economic growth and equitable economic development, each region has to determine its regional economic growth centre.  The existence of an economic growth center allows for the concentration of economic activity, which in turn has a ripple effect on the surrounding areas (Hinterland). This study was carried out to identify the primary centres of economic growth in Kendari and analyse their interactions and influence on the surrounding hinterland. This study employed both primary and secondary data, which were analysed using scalogram analysis, centrality index analysis, and gravity analysis. The findings indicate that among the eleven sub-districts in Kendari, three of them, namely Kadia, Kendari Barat, and Mandonga, serve as economic growth centres. Each economic growth centre is connected with a primary hinterland that exhibits the highest level of attraction or interaction value when compared to other districts. Among these centres, Kadia is the sub-district with the higher growth centre hierarchy and it has the highest interactions with Wua-wua. The interaction value between Kadia and Wua-wua is 139595130.7. Kendari Barat is the second growth centre in terms of its interactions with Mandonga, with an interaction value of 710383315.6. Mandonga is the third growth centre that has the highest level of interaction with Kendari Barat, with an interaction value of 710383315.6. The implication of the study is to formulate more targeted policies based on strong empirical evidence.